Outbound linkage and inbound leverage for emerging multinationals: A signaling theory perspective. (Asia Pacific Journal of Management(SSCI), 2018)
Despite the rise of interest in emerging market multinationals (EMNEs), the question of whether outward foreign direct investment (FDI) influences their resource acquisition in home countries remains underexplored. Contrary to the prior literature, which contends that EMNEs build outbound linkage through outward FDI so as to leverage outbound resources, this paper, however, focuses on whether outbound linkage influences their inbound resource leverage from home countries as well. Drawing on signaling theory, we propose that outbound linkage to developed countries, developing countries, and tax havens via outward FDI may reflect EMNEs’ different quality and prospects, which in turn influence their inbound leverage of government, financial, and market resources, respectively. Using panel data of 581 Chinese listed firms during the period 2002–2012, we largely verified our hypotheses, thus extending the boundary of the consequences of outward FDI on EMNEs in the signaling theory perspective.